What Can Mushroom Proteins Teach Us about Lipid Rafts? - Maja Grundner; Anastasija Panevska; Kristina Sepčić; Matej Skočaj (Membranes, 2021)
The lipid raft hypothesis emerged as a need to explain the lateral organization and behavior of lipids in the environment of biological membranes. The idea, that lipids segregate in biological membranes to form liquid-disordered and liquid-ordered states, was faced with a challenge: to show that lipid-ordered domains, enriched in sphingomyelin and cholesterol, actually exist in vivo. A great deal of indirect evidence and the use of lipid-binding probes supported this idea, but there was a lack of tools to demonstrate the existence of such domains in living cells. A whole new toolbox had to be invented to biochemically characterize lipid rafts and to define how they are involved in several cellular functions. A potential solution came from basic biochemical experiments in the late 1970s, showing that some mushroom extracts exert hemolytic activities. These activities were later assigned to aegerolysin-based sphingomyelin/cholesterol-specific cytolytic protein complexes. Recently, six sphingomyelin/cholesterol binding proteins from different mushrooms have been identified and have provided some insight into the nature of sphingomyelin/cholesterol-rich domains in living vertebrate cells. In this review, we dissect the accumulated knowledge and introduce the mushroom lipid raft binding proteins as molecules of choice to study the dynamics and origins of these liquid-ordered domains in mammalian cells.